Long-Term Outcome of Kidney Transplantation in Children According to Type of Transplantation in Mashhad, Iran: The outcome of kidney transplantation in Mashhad - Ravanshad, Yalda; Ghodsi, Alireza; Golsorkhi, Mohaddeseh; Azarfar, Anoush; Ravanshad, Sahar; Heidarzadeh, Samaneh; Ghodsi, Hamidreza; Tasbandi, Aida (Journal of Pediatric Nephrology, 2021)
Background and Aim: Kidney transplantation is the preferred treatment modality for end-stage renal disease (ESRD) in children. Despite its benefits and advances that have been accomplished, pediatric kidney transplantation remains a challenge in terms of achieving a satisfactory outcome. We sought to evaluate the outcome of pediatric kidney transplantation in Mashhad. Methods: Data were acquired retrospectively from children below 18 years old who underwent kidney transplantation in three main hospitals of Mashhad from 2000 to 2014. After obtaining written informed consent from parents, data were collected using a questionnaire and analyzed with the SPSS software. Results: Of 52 children, 51.9% were boys and 48.1% were girls with a mean age of 13.3 ± 4.3 years. Among them, 8 (15.4%) children received transplants from relative live donors, 16 (30.8%) from non-relative live donors, and 28 (53.8%) from deceased donors. The most common etiology leading to ESRD in these children was reflux nephropathy in 18 (34.6%) patients. After a 5-year follow-up period, the graft survival rate was 69.2% with infection being the most common cause of transplant rejection. Moreover, 13.5% of children died, mostly due to surgical complications. Conclusion: We found that to increase the survival rate of pediatric kidney transplantation in Mashhad, first the surgical methods should be enhanced as they were recognized as the most common cause of death. In addition, infection control in children, as the most common cause of transplant rejection, should be improved.